Curatorial practice of and for the tragic memory. Contributions to a state of the question - Chaquilano Falcón, Andrés Antonio (2024)
Museology applied to expositionally represent and symbolize historical acts of violence has been generating new dynamics in contemporary curatorial processes that are weakly explored and discussed in the academic scene. In this sense, the objective of this article is to contribute to the characterization of the current state of knowledge of curatorial practice aimed at the creation of museum spaces of and for tragic memories. In order to explore the interpretative forms of this phenomenon, the hermeneutic method was developed that allowed us to: (i) systematize the compiled bibliography, (ii) categorize and analyze its study themes to (iii) interpret and discuss them. This research allows us to conclude that studies of the curatorial practice of memory require analyzing each integral aspect of its materialization, that is, from the planning phases to the phases that define the exhibition, also its impacts on the public, its legitimations and struggles.